Do Termites Avoid Carcasses? Behavioral Responses Depend on the Nature of the Carcasses - Neoh, Kok-Boon; Yeap, Beng-Keok; Tsunoda, Kunio; Yoshimura, Tsuyoshi; Lee, Chow-Yang (PLOS ONE, 2012)
Background Undertaking behavior is a significant adaptation to social life in enclosed nests. Workers are known to remove dead colony members from the nest. Such behavior prevents the spread of pathogens that may be detrimental to a colony. To date, little is known about the ethological aspects of how termites deal with carcasses. Methodology and Principal Findings In this study, we tested the responses to carcasses of four species from different subterranean termite taxa: Coptotermes formosanus Shiraki and Reticulitermes speratus (Kolbe) (lower termites) and Microcerotermes crassus Snyder and Globitermes sulphureus Haviland (higher termites). We also used different types of carcasses (freshly killed, 1-, 3-, and 7-day-old, and oven-killed carcasses) and mutilated nestmates to investigate whether the termites exhibited any behavioral responses that were specific to carcasses in certain conditions. Some behavioral responses were performed specifically on certain types of carcasses or mutilated termites. C. formosanus and R. speratus exhibited the following behaviors: (1) the frequency and time spent in antennating, grooming, and carcass removal of freshly killed, 1-day-old, and oven-killed carcasses were high, but these behaviors decreased as the carcasses aged; (2) the termites repeatedly crawled under the aging carcass piles; and (3) only newly dead termites were consumed as a food source. In contrast, M. crassus and G. sulphureus workers performed relatively few behavioral acts. Our results cast a new light on the previous notion that termites are necrophobic in nature. Conclusion We conclude that the behavioral response towards carcasses depends largely on the nature of the carcasses and termite species, and the response is more complex than was previously thought. Such behavioral responses likely are associated with the threat posed to the colony by the carcasses and the feeding habits and nesting ecology of a given species.